2017
DOI: 10.1002/ece3.3328
|View full text |Cite
|
Sign up to set email alerts
|

Birds on the move in the face of climate change: High species turnover in northern Europe

Abstract: Species richness is predicted to increase in the northern latitudes in the warming climate due to ranges of many southern species expanding northwards. We studied changes in the composition of the whole avifauna and in bird species richness in a period of already warming climate in Finland (in northern Europe) covering 1,100 km in south–north gradient across the boreal zone (over 300,000 km2). We compared bird species richness and species‐specific changes (for all 235 bird species that occur in Finland) in ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 53 publications
6
29
0
1
Order By: Relevance
“…For the other diet guilds, none of the biased phylogenetic fields were observed. Although the effects of habitat preferences or dietary guild on phylogenetic structure of bird assemblages were rarely examine, several studies showed higher population fluctuation (Barshep et al, 2017) and also population decline (Virkkala & Lehikoinen, 2017) for the bird species in wetland. Kissling, Sekercioglu, and Jetz (2011) reported that global distribution of bird species richness showed pronounced differences between foraging guilds.…”
Section: Discussionmentioning
confidence: 99%
“…For the other diet guilds, none of the biased phylogenetic fields were observed. Although the effects of habitat preferences or dietary guild on phylogenetic structure of bird assemblages were rarely examine, several studies showed higher population fluctuation (Barshep et al, 2017) and also population decline (Virkkala & Lehikoinen, 2017) for the bird species in wetland. Kissling, Sekercioglu, and Jetz (2011) reported that global distribution of bird species richness showed pronounced differences between foraging guilds.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicate an overall high species turnover rate in birds in northern Europe due to climate change and other human influence (Virkkala & Lehikoinen, 2017). In other words, while northern land bird species are declining and their range is retreating north, southern species are increasing and spreading north (Reif, 2013;Virkkala & Rajasärkkä, 2011).…”
Section: Breeding Distribution Typementioning
confidence: 99%
“…Therefore, the expanding of the range boundaries of �animal) species reflects the capabilities of their peripheral populations to adapt under new environmental conditions (Melnikov & Durnev, 2012). Climate changes also affect the status of species populations �Şekercioğlu et al, 2012;Velásquez� Tibatá et al, 2013) and, as a consequence, the d�nam-ics of the boundaries of the natural distribution of birds �Crick, 2004; Araújo et al, 2011;Velásquez�Tibatá et al, 2013;Virkkala & Lehikoinen, 2017). For example, changes in the boundaries of bird ranges (Thomas & Lennon, 1999;Brommer, 2004;�assal, 2017) or a change in the arrival timing of migratory birds (Kullberg et al, 2015;Courter, 2017) have been established under the influence of various climatic factors.…”
Section: Introductionmentioning
confidence: 99%